A rights-based perspective: Refugee camps as liminal landscapes of displacement in the Anthropocene - Demirel, Abdullah Eren (Journal of landscape architecture (Wageningen, Netherlands), 2024)
The planetary-scale mobility and displacement of populations marking the Anthropocene have led to the proliferation of refugee camps as political and spatial responses to emergencies. Originally conceived as temporary facilities to provide immediate protection and control, the underlying notions of containment and temporality in refugee camps raise numerous paradoxes and questions regarding the political and humanitarian motives behind them, as well as the quality of spatial responses. However, the spatial dynamics of these camps, particularly their relationship with the ground, have not been thoroughly examined. Accordingly, this study aims to elaborate on the spatiality of refugee camps as liminal landscapes of displacement, adopting a rights-based perspective in which landscape is understood as a fundamental structure of justice in meeting the refugees' basic rights. In this context, six refugee camps are analysed regarding landscape dynamics, including ground, infrastructural and ecological relations. The findings demonstrate that the right-to-landscape perspective enhances the multiscalar and process-oriented understanding of refugee camps, benefiting both the refugees and host communities.